Estudo longitudinal de parâmetros clínicos e inflamatórios na esclerose lateral amiotrófica - Laura de Godoy Russeff Prado (2017)
Objective: To assess patients with amyotrophic lateral sclerosis (ALS) in order to verify possible associations between clinical features and inflammatory markers. Method: A consecutive series of patients with probable or defined sporadic ALS, according to Awajis criteria, underwent clinical and psychiatric (anxiety and depression questionnaires) assessment and blood analysis. A subset of these patients underwent a new assessment after 6-12 months. A sample of blood of matched controls was collected for comparison of groups. Serum levels of chemokines and cytokines were measured. Results: Of the 68 enrolled patients, 38 cases (56%) were male. The mean age at onset of symptoms was 55 years (SD ± 12.7). The average of disease duration at assessment was 3 years (SD ± 2.7). Regarding the initial form, 79% of the cases were appendicular and 21% were bulbar. About one-third of the patients had probable anxiety or depression. Symptoms of anxiety and depression were highly correlated. When comparing patients and controls, a significant increase of IL-6, IL-10 and IL-17 was found in patients. Logistic regression analysis has found a significant difference regarding age, TNF and IL-10. Of the 68 patients, 24 were assessed twice. When comparing these patients at two-time points, there was a significant decrease of RANTES in the second assessment. Older age of onset was the only variable that predicted a faster rate of disease progression. Conclusion: The clinical profile of our patients is similar to literature data. Symptoms of anxiety and depression were frequent and correlated positively. None of the inflammatory markers influenced on predicting disease course. Older age of onset predicted a faster rate of disease progression. IL-10 and TNF may be considered for a future biomarker panel for ALS diagnosis